The Effects of Ramadhan Fasting on Clinical Symptoms in Patients with Gastroesophageal Reflux Disease - Radhiyatam Mardhiyah; Dadang Makmun; Ari Fahrial Syam; Siti Setiati (Acta Medica Indonesiana)
Aim: to determine the effects of Ramadhan fasting on GERD symptoms. Methods: a total of 130 GERD patients participated in this study. Patients were divided into two groups, i.e. those who performed Ramadhan fasting (n=66), and those who did not perform Ramadhan fasting (n=64). The evaluation was done using Indonesian version of GERD questionnaire (GERD-Q) between the two groups, and between Ramadhan month and non-Ramadhan month in the Ramadhan fasting group. Results: there was a statistically significant difference (p<0.01) in the median of GERD-Q score in Ramadhan-fasting group subjects and non-Ramadhan-fasting group subjects (0 vs. 4). Moreover, a statistically significant difference (p<0.01) was also found in the median of GERD-Q score in Ramadhan-fasting group subjects and non-fasting group subjects (p<0.01). Conclusion: subjects in Ramadhan fasting group, GERD symptoms experienced less severe during fasting month (Ramadhan) than non-fasting month. During Ramadhan month, GERD symptoms were also milder in Ramadhan fasting group than those in non-fasting group subjects.